Three Temptations : Medieval Man in Search of the World - Howard, Donald Roy (Princeton, NJ : Princeton University Press, 2015)
A study of the medieval idea that defined the "world" as recorded in I John 2:16-the lust of the flesh, and the lust of the eyes, and the pride of life. Conflict in Troilus and Criseyde, Piers Plowman, and Sir Gawain and the Green Knight is explored.Originally published in 1966.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- ACKNOWLEDGMENTS -- CONTENTS -- ABBREVIATIONS -- INTRODUCTION -- CHAPTER ONE. Medieval Literature and the History of Ideas -- CHAPTER TWO. The Three Temptations -- CHAPTER THREE. Courtly Love and the Lust of the Flesh: Troilus and Criseyde -- CHAPTER FOUR. The Body Politic and the Lust of the Eyes: Tiers Plowman -- CHAPTER FIVE. Chivalry and the Pride of Life: Sir Gawain and the Green Knight -- CHAPTER SIX. The Search for the World -- INDEX
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: English poetry -- Middle English, 1100-1500 -- History and criticism; Temptation; LITERARY CRITICISM / General